The Crime of Corruption in Social Assistance Funds (Bansos) Amid the Pandemic Era in Indonesia (Case Study of the Central Jakarta District Court Decision No. 29/Pid.Sus-TPK/2021/PN.JKT.PST) - Abrar Jatnika Putra; Sadino Sadino (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This legal research is motivated by the existence of criminal acts of corruption in the midst of the pandemic. The first problem in this research is whether the decision is appropriate to ensnare the defendants of social assistance corruption. And secondly, how can the perpetrators get relief from the elements of accepting bullying from the community. This research uses normative juridical methods and types of library research, namely by examining various types of materials originating from several statutory regulations and books. The results obtained from this research are first, the form of applying the law to perpetrators in accordance with Article 12 letter b of Law of the Republic of Indonesia Number 31 of 1999 concerning the Eradication of Corruption Crimes as amended in Law Number 20 of 2001 on Corruption Crimes in conjunction with Article 55 paragraph (1 ) 1st of the Criminal Code in conjunction with Article 64 paragraph (1) of the Criminal Code. Juliari is said to have been proven to have committed corruption in the procurement of social assistance packages for handling Covid-19 in the Jabodetabek area in 2020 worth IDR 32.48 billion. So the defendant should receive a heavier sentence than the statutory regulations. Second, apart from that, the panel of judges' decision in imposing criminal sanctions must consider mitigating and aggravating factors for the defendant. The legal considerations handed down by the judge against the defendant in this case were in line with criminal law. In connection with all the elements being fulfilled legally and convincingly according to the law, it can be concluded that the elements of criminal acts of corruption regarding social assistance are fulfilled